Efficacy, Kinetics, and Mechanism of Tetracycline Degradation in Water by O3/PMS/FeMoBC Process - Xuemei Li; Qingpo Li; Xinglin Chen; Bojiao Yan; Shengnan Li; Huan Deng; Hai Lu (Nanomaterials)
This study investigated the degradation efficacy, kinetics, and mechanism of the ozone (O3) process and two enhanced O3 processes (O3/peroxymonosulfate (O3/PMS) and O3/peroxymonosulfate/iron molybdates/biochar composite (O3/PMS/FeMoBC)), especially the O3/PMS/FeMoBC process, for the degradation of tetracycline (TC) in water. An FeMoBC sample was synthesized by the impregnation–pyrolysis method. The XRD results showed that the material loaded on BC was an iron molybdates composite, in which Fe2Mo3O8 and FeMoO4 accounted for 26.3% and 73.7% of the composite, respectively. The experiments showed that, for the O3/PMS/FeMoBC process, the optimum conditions were obtained at pH 6.8 ± 0.1, an initial concentration of TC of 0.03 mM, an FeMoBC dosage set at 200 mg/L, a gaseous O3 concentration set at 3.6 mg/L, and a PMS concentration set at 30 μM. Under these reaction conditions, the degradation rate of TC in 8 min and 14 min reached 94.3% and 98.6%, respectively, and the TC could be reduced below the detection limit (10 μg/L) after 20 min of reaction. After recycling for five times, the degradation rate of TC could still reach about 40%. The introduction of FeMoBC into the O3/PMS system significantly improved the TC degradation efficacy and resistance to inorganic anion interference. Meanwhile, it enhanced the generation of hydroxyl radicals (•OH) and sulfate radicals (SO4•−), thus improving the oxidizing efficiency of TC in water. Material characterization analysis showed that FeMoBC has a well-developed porous structure and abundant active sites, which is beneficial for the degradation of pollutants. The reaction mechanism of the O3/PMS/FeMoBC system was speculated by the EPR technique and quenching experiments. The results showed that FeMoBC efficiently catalyzed the O3/PMS process to generate a variety of reactive oxygen species, leading to the efficient degradation of TC. There are four active oxidants in O3/PMS/FeMoBC system, namely •OH, SO4•−, 1O2, and •O2−. The order of their contribution importance was •OH, 1O2, SO4•−, and •O2−. This study provides an effective technological pathway for the removal of refractory organic matter in the aquatic environment.